A TAPS interactive multimedia package to solve engineering dynamics problem - Sidhu S.M.; Selvanathan N. (2023)
Purpose - To expose engineering students to using modern technologies, such as multimedia packages, to learn, visualize and solve engineering problems, such as in mechanics dynamics. Design/methodology/approach - A multimedia problem-solving prototype package is developed to help students solve an engineering problem in a step-by-step approach. A learning architecture model for developing an interactive technology-assisted problem solving (TAPS) package for visualizing engineering concepts has been discussed. Findings - The learning model was found to be easy to follow and use and the engineering package can be designed in an easy and visually appealing format. The TAPS package implemented and described in this paper could support and provide students with a better understanding of the basic concepts in an engineering mechanics dynamics course in particular. Research limitations/implications - The evaluation of the TAPS package materials comprised mainly quantitative methods which provided validation of the package approach for the acquisition of procedural skills and related basic concepts. More work is necessary to employ qualitative approaches for more detailed analysis of usability of particular materials of the TAPS package. Originality/value - The main originality of the paper can be seen from the development of the package that guides the student intelligently to solve the selected engineering problem. In addition, important user tools are also included which the user may need to use if necessary. Emerald Group Publishing Limited.